2006
DOI: 10.1016/j.visres.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of accommodative behavior during sustained reading in emmetropes and myopes

Abstract: Accommodation has long been suspected to be involved in the development of myopia because near work, particularly reading, is known to be a risk factor. In this study, we measured several dynamic characteristics of accommodative behavior during extended periods of reading under close-to-natural conditions in 20 young emmetropic and stable myopic subjects. Accommodative responses, errors, and variability (including power spectrum analysis) were analyzed and related to accommodative demand and subject refractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
131
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 80 publications
13
131
2
1
Order By: Relevance
“…30 The PowerRefractor recorded at 25 Hz, and the data were exported to Microsoft Excel (Microsoft, Redmond, WA) and were filtered for blinks by removing refractive changes >10 D/s. 31 The median accommodative response was used for the PowerRefractor data to minimize the effect of potential outliers, as there were more fluctuations when recording continuously than when doing five individual measurements with autorefraction.…”
Section: Recruitment Enrollment and Data Collectionmentioning
confidence: 99%
“…30 The PowerRefractor recorded at 25 Hz, and the data were exported to Microsoft Excel (Microsoft, Redmond, WA) and were filtered for blinks by removing refractive changes >10 D/s. 31 The median accommodative response was used for the PowerRefractor data to minimize the effect of potential outliers, as there were more fluctuations when recording continuously than when doing five individual measurements with autorefraction.…”
Section: Recruitment Enrollment and Data Collectionmentioning
confidence: 99%
“…In recent years, numerous epidemiological surveys of adolescent myopia have suggested that environmental factors, especially sustained near visual work might be one of the main reasons for the occurrence and development of myopia [6][7][8][9][10][11][12][13][14][15][16]. A recent study suggested that near-workinduced myopia might be linked to the over-responses of accommodation and convergence during near-distance gazing [17][18][19][20].…”
mentioning
confidence: 99%
“…Diagnostic criteria and measurement protocols here mirror those of Scheiman et al, (Scheiman et al 1996) however in sampling only young myopes, and presumably some percentage of whom are progressing, these results are in alignment with the previously demonstrated higher frequency of inaccurate accommodative and vergence behaviours in myopic children and young adults compared to their emmetropic counterparts -in particular esophoria at near, accommodative lag and increased accommodative convergence (AC/A ratio). (Gwiazda et al 1995a, Abbott et al 1998, Harb et al 2006 After commencement of OK wear, as the group mean became more exophoric, 3 of the initial 10 esophores remained as such; 6 moved from esophoria to normal range; one moved from esophoria to exophoria and 3 moved from normal to exophoric. An exophoric shift has been associated with stabilisation of childhood myopia progression (Goss and Wolter 1999) hence this could be part of OK's demonstrated propensity for myopia control.…”
Section: The Effect Of Age and Frequency Of Bv Disordersmentioning
confidence: 99%
“…There is a reported association between higher levels of esophoria and accommodative lag at near in myopic children and young adults as compared to emmetropes. (Drobe and de Saint-André 1995, Nakatsuka et al 2005, Allen and O'Leary 2006 Myopic children and young adults also show insufficient accommodative responses to lens-induced blur, (Bullimore et al 1992, Abbott et al 1998, Pandian et al 2006 greater variability in accommodative response (Harb et al 2006), reduced accommodative facility O'Leary 2006, Pandian et al 2006) and enhanced accommodative convergence (elevated AC/A ratios) when compared to age matched emmetropes. , Mutti et al 2000b Conjecture exists, though, as to whether accommodative errors are a feature rather than a cause of myopia.…”
Section: Binocular Vision and Myopiamentioning
confidence: 99%
See 1 more Smart Citation